X-Ray Diffraction and Dielectric Spectroscopy of Poly(ethylene terephthalate) and PET/Carbon Nanotube Nanocomposites - Stenger, Bret. (Tufts Archival Research Center, 2005)
The crystallization of poly(ethylene terephthalate) (PET) and a nanocomposite of PET with multi-walled carbon nanotubes (MWCNTs) were studied by wide and small angle X-ray diffraction and dielectric relaxation spectroscopy. The purpose was to differentiate between a heterogeneous and homogeneous stack model to describe the lamellar organization in PET and to determine the effect of carbon nanotubes on the crystal growth in PET. The nanocomposites contained 2% MWCNT by weight, and were prepared by solution mixing, and then compression molding into film. Dielectric measurements were made at frequencies from 100 Hz to 1 MHz, in parallel plate geometry. Measurements of the samples during cold crystallization (100-120°C) were used to investigate the relationship between the growth of crystals and the restriction of the molecular mobility of the amorphous phase. Results indicate that a heterogeneous distribution of amorphous regions exists, implying both interlamellar and interfibrillar/interspherulitic placement of the amorphous chains. Addition of carbon nanotubes to the PET increased the rate of cold crystallization, but did not affect the glass transition relaxation process.